Effects of argon atoms in excited states on properties of argon-acetylene dusty plasma - Denysenko, I.B.; Ivko, S.; Azarenkov, N.A.; Burmaka, G. (Вопросы атомной науки и техники, 2020)
It is studied how dissociation and ionization of acetylene molecules in their collisions with argon atoms in excited states Ar* may affect properties of argon-acetylene plasma with growing inside of plasma volume dust particles. The study is carried out using a volume-averaged model. To analyze the effects of Ar* atoms on the electron and ion densities, the effective electron temperature and the densities of radical and nonradical neutral species, the values of ionization and dissociation rates for collisions of acetylene molecules with Ar* atoms are varied in numerical calculations. It is found that the collisions of Ar* atoms with acetylene molecules affect essentially the argon-acetylene dusty plasma. Досліджено, як дисоціація та іонізація молекул ацетилену при їх зіткненні з атомами аргону в збудженому стані Ar* можуть впливати на властивості аргон-ацетиленової плазми зі зростаючими всередині плазмового об’єму порошинками. Дослідження проведено за допомогою просторово-усередненої моделі. Для аналізу впливу атомів Ar* на густину електронів та іонів, ефективну температуру електронів та густину радикальних і нерадикальних нейтральних частинок значення коефіцієнтів іонізації і дисоціації для зіткнень молекул ацетилену з атомами Ar* у численних розрахунках варіювалися. Встановлено, що зіткнення атомів Ar* з молекулами ацетилену істотно впливають на запорошену аргон-ацетиленову плазму. Исследовано, как диссоциация и ионизация молекул ацетилена при их столкновении с атомами аргона в возбужденном состоянии Ar* могут влиять на свойства аргон-ацетиленовой плазмы с растущими внутри плазменного объема пылевыми частицами. Исследование проведено с помощью пространственно- усредненной модели. Для анализа влияния атомов Ar* на плотность электронов и ионов, эффективную температуру электронов и плотность радикальных и нерадикальных нейтральных частиц значения коэффициентов ионизации и диссоциации для столкновений молекул ацетилена с атомами Ar* в численных расчетах варьировались. Установлено, что столкновения атомов Ar* с молекулами ацетилена существенно влияют на пылевую аргон-ацетиленовую плазму.